Canada–EU relations in political sphere - Антохів-Сколоздра, О. М.; Antokhiv-Skolozdra, Olesya; Antokhiv-Skolozdra, O. M. (Одеса, 2020)
The article considers the peculiarities of formation and development of relations between Canada and the European Union in political sphere. It points out that the common essence of approaches to modern international relations serves as a potential basis for building bilateral cooperation on the issues of establishing political cooperation. In the course of research on Canada’s foreign policy it was noted that there is a number of features that are due to both internal context and external factors. In particular, it refers the peculiar nature of Canadian statehood, the existence of two linguistic communities, geographical location, and immediate neighborhood with the United States. It emphasizes the similarity of Canada’s positions with the approaches of European countries to solving a number of problems of modern world development. The importance of maintaining the transatlantic connection is among the significant issues. At the same time, it should be taken into account that there are peculiarities of establishing and maintaining relations between Canada and the European Union. On the one hand these are the relations with a strong multinational association and on the other – with each individual member state. It is noted that, despite the long historical tradition in the relationship, the potential for cooperation between Canada and the EU is only partially used. It highlights the need for Canada to reach a new level in its relations with the European Union, provided that it maintains close relations with the United States of America. Areas of mutual interest, as well as problematic aspects of negotiations on a strategic partnership agreement between Canada and the European Union have been identified. Although Canada–EU relations are bilateral, they are evolving in a broader international context. It is analyzed that Canada can be a valuable partner for the European Union in the field of international relations. This country should strive to be involved in the preparation of important international decisions in order to build common positions and ensure a sufficient level of coordination between the parties.

У статті розглянуто особливості становлення та розвитку відносин між Канадою та Європейським Союзом у політичній сфері. Зазначено, що нормативна спільність підходів до сучасних міжнародних відносин є потенційною основою для розбудови двосторонньої взаємодії з питань налагодження політичної співпраці. Зазначено, що вивчення зовнішньої політики Канади вирізняється низкою особливостей, які обумовлені як внутрішнім контекстом, так і зовнішніми чинниками. Зокрема, йдеться про своєрідний характер канадського державотворення, наявність двох лінгвістичних спільнот, географічне положення, безпосереднє сусідство зі Сполученими Штатами. Наголошено на збіжності позицій Канади з підходами держав Європи до вирішення низки проблем сучасного світового розвитку. Підкреслено важливість збереження трансатлантичного зв’язку. Водночас варто зважати на особливості побудови та підтримки відносин між Канадою та Європейським Союзом як із потужним багатонаціональним об’єднанням, так і з окремою державою-членом. Зазначено, що, незважаючи на тривалу історичну традицію у відносинах, потенціал взаємодії Канади і ЄС використовується лише частково. Наголошено на необхідності для Канади виходу у взаєминах з Євросоюзом на новий рівень за умови збереження тісних відносин зі Сполученими Штатами Америки. Визначено сфери взаємного зацікавлення, а також проблемні аспекти перемовин щодо угоди про стратегічне партнерство Канади та Європейського Союзу. Відносини між Канадою та ЄС є двосторонніми, однак вони розвиваються у ширшому міжнародному контексті. Доведено, що Канада у сфері міжнародних відносин може бути цінним партнером для Євросоюзу. Цій країні варто прагнути до залучення у процес підготовки важливих рішень міжнародного характеру для розбудови спільних позицій та забезпечення достатнього рівня координації зусиль сторін.
Antokhiv-Skolozdra O. M. Canada–EU relations in political sphere / O. M. Antokhiv-Skolozdra // Актуальні проблеми філософії та соціології : Науково-практичний журнал / Голов. ред. С. Г. Секундант, відпов. ред. Д. В. Яковлев ; Міністерство освіти і науки України ; Національний університет "Одеська юридична академія". - Одеса, 2020. - Вип. 27. - С. 140-145. DOI https://doi.org/10.32837/apfs.v0i27.935
Keywords: Canada; European Union; political cooperation; bilateral relations; transatlantic cooperation; multilateralism; Канада; Європейський Союз; політична співпраця; двосторонні відносини; трансатлантична співпраця; мультилатералізм; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Political science